The Natural Composite of Sawdust Teak as a Sound Absorption Materials Using The Resonator Space Method - Yulita Nurbaiti; Agus Yulianto; Upik Nurbaiti (Physics Education Research Journal, 2022)
The development of science and technology has resulted in the increasing use of sophisticated equipment that can produce unwanted sounds, resulting in noise. Acoustic materials are a solution that can reduce noise. This study aims to determine the sound absorption coefficient of a composite of teak sawdust and polyester resin as an environmentally friendly acoustic material. The sample was made in the form of a cylinder using a press of as many as six samples with a comparison of the mass fraction of teak sawdust and the mass fraction of polyester resin, namely sample 1 (30:70), sample 2 (40:60), sample 3 (50:50), sample 4 (60:40), sample 5(70:30), sample 6(80:20). The samples that have been made were tested using a resonance space and sound level meter to measure the value of the sound absorption coefficient (α) at frequencies of 500 Hz, 1000 Hz, 1500 Hz, 2000 Hz, 2500 Hz, and 3000 Hz. The optimal acoustic material sample in sample 1 with a fiber mass fraction of 30% and a sound absorption coefficient of 0.707 at a frequency of 3000 Hz.